Generation of Synthetic Streamflow of Jakham River, Rajasthan Using Thomas-Fiering Model - Sharma, Priyanka; Bhakar, S. R.; Ali, Shakir; Jain, H. K.; Singh, P. K.; Kothari, Mahesh (Journal of Agricultural Engineering, 2019)
A study was undertaken to develop and apply Thomas-Fiering (T-F) model for generation of synthetic streamflow of Jakham river, Rajasthan. Streamflow data of 40 years (June,1975 to May, 2015) was used, of which 360 month-data (June,1975 to May, 2005) were used to develop the model and 120 month-data (June, 2005 to May, 2015) were used to predict the streamflow. Performance of the model was evaluated using four statistical criteria, viz. correlation coefficient (R), root mean square error (RMSE), modified Nash-Sutcliffe efficiency (MNSE), and modified index of agreement (MIA).The results showed satisfactory performance of the model in generating synthetic monthly streamflow based on R, RMSE, MNSE and MIA values of 0.73, 28.47Ã—106 m3, 0.456 and 0.73, respectively. The developed model was used to generate 100-year synthetic streamflows.